2010
DOI: 10.1080/15287394.2010.491044
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds in the Human Diet and their Ability to Bind Mutagens Prevents DNA–Mutagen Intercalation

Abstract: Human diet may contain many mutagenic or carcinogenic aromatic compounds as well as some beneficial physiologically active dietary components, especially plant food phytochemicals, which act as mutagenesis or carcinogenesis inhibitors. This study compared the binding properties of natural compounds in the human diet (caffeine, theophylline, theobromine, and resveratrol) with a water-soluble derivative of chlorophyll to bind to acridine orange, a known mutagen. An analysis was conducted to determine which subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…The "interceptor" mode of CAF was described and analyzed for HCAs [15] and several other aromatic compounds: ethidium bromide [20,21], propidium iodide [19,20], quinacrine mustard, ICR170, ICR191 [22], proflavine [23], and several anticancer drugs [17,24,25]. Similar mechanism was also described for interaction of chlorophyllin (CHL) [26] and other natural constituents of human diet [27] with several aromatic compounds. It was demonstrated that CHL forms stacking heterocomplexes with HCAs and in consequence diminishes their mutagenic activity and reduces their absorption from gastrointestinal tract [28,29].…”
Section: Mechanism Of Heterocomplexationmentioning
confidence: 99%
See 1 more Smart Citation
“…The "interceptor" mode of CAF was described and analyzed for HCAs [15] and several other aromatic compounds: ethidium bromide [20,21], propidium iodide [19,20], quinacrine mustard, ICR170, ICR191 [22], proflavine [23], and several anticancer drugs [17,24,25]. Similar mechanism was also described for interaction of chlorophyllin (CHL) [26] and other natural constituents of human diet [27] with several aromatic compounds. It was demonstrated that CHL forms stacking heterocomplexes with HCAs and in consequence diminishes their mutagenic activity and reduces their absorption from gastrointestinal tract [28,29].…”
Section: Mechanism Of Heterocomplexationmentioning
confidence: 99%
“…The latter mechanism, as described before, reduces mutagenic potential of aromatic mutagens by formation of molecular complexes with aromatic mutagens, thus reducing their bioavailability. Such effects were described for one of the model mutagens, acridine orange, and resveratrol by Osowski et al [27].…”
Section: Role Of Polyphenolsmentioning
confidence: 99%
“…Hetero-association in Drug-xanthine systems has been extensively studied by NMR, UV-vis, Fluorescence spectroscopies, titration microcalorimetry, partitioning in waterorganic mixture, molecular modelling and other techniques for the following aromatic drugs: daunomycin (DAU) [127,[133][134][135][136], doxorubicin (DOX) [33,42,127,[137][138][139], actinomycin D (AMD) and its derivatives [133,[140][141][142][143], benzene and its derivatives [122,144], novantrone/mitoxantrone (NOV) [42, 127, 135-137, 145, 146], nogalamycin (NOG) [138], norfloxacin (NOR) [135,136,147], camptothecins [139,148,149], quinoxaline [84], chloroquine [84], DAPI [150], phenothiazines [121,151,152], riboflavin [135,[153][154][155], porphyrins [156,157], acridine mutagens [53,54,124,125,[133][134]…”
Section: Drug-xanthine Systemmentioning
confidence: 99%
“…It was concluded that complexation of aromatic ligands with xanthines results from π-π stacking at pH close to neutral, which is based on systematic NMR magnetic shielding of aromatic protons of xanthine (or a drug) on increasing the concentration of the drug (or a xanthine) [115, 122, 133-135, 138, 145, 147, 149, 163], on specific changes in absorption of the drug in the visible range of the spectrum (hypochromic and bathochromic shifts) on increasing the concentration of xanthine [42, 53, 54, 124, 128, 137, 150-152, 157, 159] and on red-shifts in the absorption/emission bands in fluorescence [53,137,140,157]. The overwhelming majority of published NMR work on hetero-association reports that π-stacking affects the value of chemical shift, except in a few very rare examples, e.g.…”
Section: Drug-xanthine Systemmentioning
confidence: 99%
See 1 more Smart Citation